THE USE OF TRANSLATION IDEOLOGY AND TECHNIQUES IN INDONESIAN VERSION OF AGATHA CHRISTIE’S ENDLESS NIGHT NOVEL - Muhammad Zaki Pahrul Hadi; Erwin Suhendra; Titik Ceriyani Miswaty (Humanitatis : Journal of Language and Literature, 2020)
Abstract Translation is a process of transfering source text into the target text viewed from the equivalent of meaning, with equvalencies, the message in the translation text will be the same as the target text. Hence, translating is not just the process of tranfering text from the source language into the target language. However, instead of ideas, translation enters compilation, he processes a translation product. The use of appropriate translation techniques also affects the quality of the translation results. This study aims to describe the ideology of translation in Indonesian Version of Agatha Christie’s Endless Night Novel. The method used in this research is descriptive qualitative. The data of this study are qualitative based on types of words, phrases and sentences containing translation techniques and ideology taken from the translated novel of Indonesian Version of Agatha Christie’s Endless Night Novel. Based on the analysis of translation techniques and the ideology of translation used in the text, the ideology used in the translation text is foreignization. Based on the analysis, the results of the study show that of the 18 translation techniques, 12 translation techniques were found consisting of; Literal translation (53%), Amplification (11%), Variation (8%), Particularization (6%), Borrowing (6%), Transposition (5%), Reduction (4%), Calque (2%), Compensation (2%). Meanwhile Description, Linguistic Compression, and Established Equivalent occur only in (1%). The result of the study shows that the most dominant technique used in Indonesian version of Agatha Christie’s endless night novel is Literal translation with 82 occurrences frequency or 53%.